Phenomenology studies in junior high school students' enthusiasm in social studies learning in Universitas Malang Laboratorium, Indonesia - Heru Wijanarko; I Dewa Putu Eskasasnanda; Bayu Kurniawan (Harmoni Sosial: Jurnal Pendidikan IPS, 2020)
Social science is a common subject given at every level of education. The Social Sciences junior high school curriculum is taught in an integrated manner to facilitate students' social science learning that is important in everyday life. Unfortunately, there are many obstacles encountered in social studies in practice, one of which is the lack of interest and enthusiasm of students in learning social studies. It makes students unable to grasp the importance of social studies. This research conduct on students and teachers of the Junior High School Laboratory State University of Malang. This study aims to analyze non-enthusiasm students in social classes learning. This research conduct using descriptive methods with survey research. Data collection techniques used are observation, interview, and documentation data collection tools in observation guidelines and interview guidelines. This study's informants were 17 students taken at each grade level and supported by three informants from social studies teachers who were selected purposes study indicates that UM Lab junior high school students' unenthusiastic behavior when learning social studies is reading comics, singing, drawing, chatting, and joking with friends. The factors that cause it are the amount of material and assignments in modules that must be memorized and memorized. Students are dizzy and confused. It has an impact on their understanding, which is less related to social studies material.